Fatigue Life Analysis of Engineered Fiber Reinforced Cementitious Composite - Lu, Yangyang (International Journal of Materials Science and Technology Studies, 2024)
As a new type of building material, Engineered Fiber Reinforced Cementitious Composite have attracted the attention of many scholars in civil engineering. They have super toughness, quasi strain hardening, and multi joint cracking characteristics. Due to the excellent characteristics of ECC, this material has been widely developed in the United States, Japan, and Europe, and has been successfully applied in multiple practical project engineering. Materials should meet fatigue reliability requirements before being put into use. Due to the large variability of fatigue life, in order to meet engineering needs, probability statistics should be used to analyze their fatigue characteristics. Compared to other continuity probability distribution models, the Weibull distribution model can better describe the fatigue life characteristics of ECC materials. Domestic and foreign scholars have conducted corresponding research on the fatigue life of ECC materials, all of which have confirmed that the fatigue performance of ECC materials is significantly better than that of ordinary concrete, and its fatigue life follows a Weibull distribution. This article will apply Weibull probability density function to derive the fatigue life of ECC materials, in preparation for subsequent experiments.